Camrelizumab combined with chemotherapy for stage IV pulmonary sarcomatoid cancer with pancreatic metastases - Liqin Ruan; Ningbo Fang; Weili chen; xiaoyong Wu; Xin hua Zhao; Lu Wang (Respiratory Medicine Case Reports, 2024)
The pancreas is a rare metastatic site for lung cancer. We report the case of a 66-year-old male with pulmonary sarcomatoid carcinoma (PSC) with pancreatic and right posterior renal fascia metastases treated with immunotherapy and platinum-based chemotherapy. A pathological biopsy of the right posterior fascial mass showed lung invasive adenocarcinoma and sarcomatoid carcinoma metastasis. Immunohistochemistry staining showed that PD- L1 expression was high and next-generation sequencing revealed KRAS and TP53 mutations. Camrelizumab and chemotherapy were administered, and the metastasis disappeared. Immunotherapy combined with platinum-based chemotherapy is effective in treating PSC with pancreatic metastases.